2011
DOI: 10.4236/ojm.2011.12006
|View full text |Cite
|
Sign up to set email alerts
|

On a Predictive Scheme of Slow Photoconductive Gain Evolution in Epitaxial Layer/Substrate Optoelectronic Nanodevices

Abstract: The photoconductive response of the fundamental type of diodic nanodevice comprising a low resistivity, n-type epitaxial layer and a semi-insulating substrate is considered in terms of the optoelectronic parameter of photoconductive gain as experimentally measurable through monitoring the temporal evolution of conductivity current photoenhancement under continuous epilayer illumination-exposure. A modelling taking into account the built-in potential barrier of the interface of the epitaxial layer/substrate dev… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

2
5
0

Year Published

2018
2018
2020
2020

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(7 citation statements)
references
References 7 publications
2
5
0
Order By: Relevance
“…For instance, Matsuo et al observed in 1984 that the gain of GaAs photoconductive detectors predicted by the recycling gain theory is 3–4 orders of magnitude smaller than the gain measured in the experiments. Similar observations have been made persistently by other researchers in the past several decades. ,, Some argued that this disparity is due to the carrier trapping by surface trap states or charge separation by built-in electric fields that increases the recombination lifetime of minority carriers. ,, Others even mixed up the concepts of trap-emission and minority recombination lifetimes, using the long trap lifetime to replace the short minority recombination lifetime to explain away the disparity. Up to date, this gain theory is still being widely used to explain the observed photoconductive gain in photoconductors based on quantum dots, nanowires , and more recently 2-dimensional materials. , …”
supporting
confidence: 63%
See 2 more Smart Citations
“…For instance, Matsuo et al observed in 1984 that the gain of GaAs photoconductive detectors predicted by the recycling gain theory is 3–4 orders of magnitude smaller than the gain measured in the experiments. Similar observations have been made persistently by other researchers in the past several decades. ,, Some argued that this disparity is due to the carrier trapping by surface trap states or charge separation by built-in electric fields that increases the recombination lifetime of minority carriers. ,, Others even mixed up the concepts of trap-emission and minority recombination lifetimes, using the long trap lifetime to replace the short minority recombination lifetime to explain away the disparity. Up to date, this gain theory is still being widely used to explain the observed photoconductive gain in photoconductors based on quantum dots, nanowires , and more recently 2-dimensional materials. , …”
supporting
confidence: 63%
“…Similar observations have been made persistently by other researchers in the past several decades [4,11,12]. Some argued that this disparity is due to the carrier trapping by surface trap states or charge separation by built-in electric fields that increases the recombination lifetime of minority carriers [6,13,14]. Others even mixed up the concepts of trap-emission and minority recombination lifetimes [4], using the long trap lifetime to replace the short minority recombination lifetime to explain away the disparity.…”
supporting
confidence: 58%
See 1 more Smart Citation
“…3,5,15 The question is where these high gains are coming from. [16][17][18] This is because the classical theory incorrectly made a second assumption that the number of excess electrons and holes contributing to photoconductivity are equal. Although excess electrons and holes are generated in pairs, excess minority carriers are often trapped by defects or potential wells (depletion regions for instance) in semiconductors.…”
mentioning
confidence: 99%
“…However, high gains in photoconductors are often observed in experiments. ,, The question is where these high gains are coming from. This is because the classical theory incorrectly made a second assumption that the number of excess electrons and holes contributing to photoconductivity are equal. Although excess electrons and holes are generated in pairs, excess minority carriers are often trapped by defects or potential wells (depletion regions for instance) in semiconductors. , The same number of excess majority counterparts is accumulated in the conduction channel, leading to the experimentally observed high photogain …”
mentioning
confidence: 99%